Is the Olympic boardsailor an endurance athlete? - de Vito, G.; Di Filippo, L.; Rodio, A.; Felici, F.; Madaffari, A. (International Journal of Sports Medicine, 1997)
The present study was carried out in order to describe the physiological profile of top Olympic boa rdsailors of both genders and to measure the energy cost during actual boardsailing with particular attention to the most demanding conditions. Fourteen elite Olympic boardsailors (7 males and 7 females) volunteered to participate in the study. Each subject underwent a maximal cycle ergometer test in orderto measure VO2peak and ventilatory threshold (Tvent). Additionally, anthropometric measurements including body fat percentage were taken. The cardiorespiratory demand and the energy cost of actual boardsailing were assessed by means of a very light telemetric device (K2 Cosmed) which allowed the measurements of VO2, VE and HR. VO2peak was 63.6 +/- 2.3 ml x kg(-1) x min(-1) (Tvent 70% of maximum) and 49.2 +/- 4.1 (Tvent 60% of maximum) in males and females, respectively. The data recorded during actual boardsailing show that this sport activity can be classified as aerobic, the VO2 values being above or very close to those of Tvent values (75% and 60% of the maximum in males and females). Furthermore the mean blood lactate values obtained at the end of each regatta testing were 6 +/- 2 mMol x l(-1) in males and 5 +/- 1.5 mMol x l(-1) in females indicating a partial involvement of anaerobic metabolism, which in some regatta phases could represent a limiting factor for performance.